2017
DOI: 10.1038/hdy.2017.6
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale genetic structure due to adaptive divergence among microhabitats

Abstract: It has been suggested that adaptive evolution on ecological timescales shapes communities. However, adaptation among environments relies on isolation or large selection coefficients that exceed migration effects. This reliance is tempered if adaptation is polygenic-does not depend on one allele completely replacing another but instead requires small allele frequency changes at many loci. Thus, whether individuals can evolve adaptation to fine-scale habitat variation (for example, microhabitats) is not resolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 71 publications
(145 reference statements)
9
31
1
Order By: Relevance
“…A high species turnover has been associated with poor dispersal abilities (Thompson & Townsend, 2006). We found a high replacement of the species by other species among habitats (species turnover = 0.60), suggesting that a non-random migration is likely to occur among habitats caused by environmental filtering or spatial restriction, which likely promote high diversity, as previously observed in the freshwater fish, Fecunduls heteroclitus (Wagner, Baris, Dayan, Du, Oleksiak, & Crawford, 2017). However, a high species turnover could also be associated with sampling bias.…”
Section: Discussionsupporting
confidence: 72%
“…A high species turnover has been associated with poor dispersal abilities (Thompson & Townsend, 2006). We found a high replacement of the species by other species among habitats (species turnover = 0.60), suggesting that a non-random migration is likely to occur among habitats caused by environmental filtering or spatial restriction, which likely promote high diversity, as previously observed in the freshwater fish, Fecunduls heteroclitus (Wagner, Baris, Dayan, Du, Oleksiak, & Crawford, 2017). However, a high species turnover could also be associated with sampling bias.…”
Section: Discussionsupporting
confidence: 72%
“…Again, all SNPs that are significant at an FDR of 10% are also significant at the Bonferroni level and are hence displayed as the latter. Furthermore, pond:pond pairwise comparisons yield F ST outliers with similar magnitudes to basin:pond comparisons, contrary to the prior expectation of genetic divergence among distinct niches [11].…”
Section: Resultscontrasting
confidence: 57%
“…Contrary to the prediction that panmictic breeding every generation would inhibit local adaptation, previous work identified significant genetic divergence among F. heteroclitus inhabiting distinct niches less than 100m apart in three replicate estuaries/populations [11]. The authors identified single nucleotide polymorphisms (SNPs) displaying significant spatial differentiation among well-connected niches in each of three isolated estuaries and supported by three different selection tests.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations